Socjopsychologiczne mechanizmy nauczania i uczenia się języków obcych - Tyszka, Sylwia (Investigationes Linguisticae, 2011)
The article presents learning and teaching foreign languges from two perspectives: the social and psychological ones. The first subparagraph draws the attention to the social and psychological aspects of the communication at a foreign language lesson. Then is described the role of the teacher, whereas the last section shows the individual features of a language learner which influence his success in mastering a foreign language.